ANALISIS PENGARUH PROFESIONALISME DAN KOMPETENSI TERHADAP KREATIVITAS DAN DAMPAKNYA PADA KUALITAS PELAYANAN (MEDIS DAN PARAMEDIS) DI PUSKESMAS SOSOK KECAMATAN TAYAN HULU KABUPATEN SANGGAU - B2042131033, YOHANES B2042131033 (Equator Journal of Management and Entrepreneurship (EJME), 2019)
Human Resources (HR) is a central factor in a government organization. Problems occurring in Puskesmas Sosok are marked by the recipient community of service / customers who feel less satisfied with the complaints on the quality of service. From the results of observations in the work environment Puskesmas Sosok there are some apparatus who have not fully have the ability to master and understand and perform the field of duties in accordance with the profession. The researcher is interested in taking the title of "Analysis of Influence of Professionalism, Competence on Creativity and Impact on Service Quality (Medical and Paramedic) at Sosok Public Health Center of Tayan Hulu Sub-district of Sanggau Regency". The results showed that there is influence of Creativity on Service Quality (Medical and Paramedic) at Sosok Public Health Center of Tayan Hulu Subdistrict of Sanggau Regency.